Chemical Cleaning of Ultrafiltration Membrane Fouled by Humic Substances: Comparison between Hydrogen Peroxide and Sodium Hypochlorite - Li, Kai; Li, Shu; Huang, Tinglin; Dong, Chongzhe; Li, Jiawei; Zhao, Bo; Zhang, Shujia (International journal of environmental research and public health, 2019)
Chemical cleaning is indispensable for the sustainable operation of ultrafiltration (UF) system in water and wastewater treatment. Sodium hypochlorite (NaClO) is an established cleaning agent for membranes subject to organic and microbial fouling, but concerns have been raised about the generation of toxic halogenated by-products during NaClO cleaning. Hydrogen peroxide (H2O2) is a potential “green” cleaning agent that can avoid the formation of halogenated by-products. In this work, cleaning efficacy of H2O2 and NaClO for UF membrane fouled by humic substances (HS) was evaluated under a wide pH range, and change of HS’s properties due to reaction with cleaning agents was examined. The cleaning efficacy of H2O2 was lower than that of NaClO at pH 3–9, but it increased to a level (91.4%) comparable with that of NaClO at pH 11. The extents of changes in properties and fouling potential of HS due to reacting with cleaning agents were consistent with their cleaning efficacy. H2O2 treatment at pH 11 significantly increased negative charge of HS molecules, decomposed high-MW molecules, and reduced its fouling potential. Therefore, considering treatment/disposal of cleaning waste and cleaning efficacy, H2O2 cleaning under strong alkaline condition can be a good choice for HS-fouled membrane.